Efektivitas Kecerdasan Buatan VerasAI sebagai Referensi Desain Fasad Mahasiswa Arsitektur - Agi Nasrullah; Muh Fais Giffari; Taufik Hidayat. S; Fanny Siti Rabania Achmad; Muhammad Fiqri M. Muhlis (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Digital era development has supported to lighten human work these days. There is a lot of software which is acted in that case. VerasAi is one of the software which support the architecture student to find ideas/reference facade to aplly in a design. Buildang facade has important role in aextethic and building termal performance, In order to an efficient and interesting facade design become crucial in architectural practice. Methode which is used in are kualitatif deduktif that describe plug-in VerasAI application and also sharing quisoner to the architectural students which has been following Studio architecture planning and using VerasAI as a rendering tools in a design process. As results of the research are to measure the efectiveness of using VerasAI in giving facade design concept ideas for architecture students. This research also disclose that VerasAI can help to increasing time effciency in facade design process, student can explore a lot of ideas quikly and effective is possible. However, there are also some constraint of using VerasAI such as algorithm limit and lack of control over some aspects of the design. In other hand, it show how are the advantage and lack of VerasAI and impact to the architecture student.